2010
DOI: 10.1002/adsc.201000397
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Electron‐Deficient Phosphine Ligands for Direct Arylation of Heterocycles

Abstract: New electron-deficient biarylphosphine ligands were studied and proved to be efficient for the direct arylation of heteroarenes with aryl iodides. The ability of a more electron-deficient palladium centre to accelerate the arylation of heterocycles that remained unreactive with aryl iodides in the past has been validated and these heteroarenes can now be smoothly reacted in the presence of a new electrophilic catalyst. Experimental evidence suggests a viable concerted metalation-deprotonation pathway for the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(25 citation statements)
references
References 53 publications
(7 reference statements)
1
24
0
Order By: Relevance
“…In addition, direct arylation by a concerted metalation-deprotonation process, which tends to be accelerated by an electron-poor phosphine ligand, [15] was also ruled out. Indeed, phosphines bearing fluoro substituents, such as P(C 6 F 5 ) 3 , did not increase the activity of the palladium catalyst and did not show any ligand acceleration effect (Table 1, Entry 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, direct arylation by a concerted metalation-deprotonation process, which tends to be accelerated by an electron-poor phosphine ligand, [15] was also ruled out. Indeed, phosphines bearing fluoro substituents, such as P(C 6 F 5 ) 3 , did not increase the activity of the palladium catalyst and did not show any ligand acceleration effect (Table 1, Entry 6).…”
Section: Resultsmentioning
confidence: 99%
“…For chlorobenzene, Pd 0 complexes with PPh 3 or bidentate ligands such as 1,3-bis(diphenylphosphanyl)propane (dppp), 1,3-bis(diisopropylphosphanyl)propane (dippp), 1,2-bis(dicyclohexylphosphanyl)ethane (dCype), 1,1Ј-bis(di-tert-butylphosphanyl)-ferrocene (dbpf), or 4,5-bis(diphenylphosphanyl)-9,9-dimethylxanthene (Xantphos) were all inactive (Table 1, Entries [8][9][10][11][12][13][14][15]. [10] On the basis of the ability of palladium complexes of 4,6-bis(diphenylphosphanyl)phenoxazine (the NiXantphos ligand of Van Leeuwen) to effectively crosscouple organometallics with aryl chlorides, [11] the reaction was examined with 6 mol-% of this ligand.…”
Section: Resultsmentioning
confidence: 99%
“…of 4-iodotoluene gave compound 77 ( Figure 14) in 46% yield and the C-5 arylation of 72 with methyl 4-iodobenzoate gave compound 78 ( Figure 14) in 43% yield. [51] A year later, after a short ligand optimization, Daugulis and co-workers found that when NMP was used as the solvent, K 3 PO 4 was the base and the catalyst system consisted of a mixture of 5 mol% PdA C H T U N G T R E N N U N G (OAc) 2 and 10 mol% 2-(dicyclohexylphosphino)biphenyl (L4), furan (79) and its 2-substituted derivatives 48 and 49 underwent arylation at position 5 with electron-rich and electron-poor aryl chlorides as well as 2-chloropyridine in good to excellent yields (Scheme 32). [52] Ligands such as dicyclohexylphenyl-, tricyclohexyl-and n-butyl-bis(1-adamantyl)phosphine proved to be not effective.…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 97%
“…of Ag 2 CO 3 as the promoting agent, DMA as the solvent and a catalyst system composed of 5 mol% PdA C H T U N G T R E N N U N G (OAc) 2 , 10 mol% electron-deficient phosphane ligand L3 and 30 mol% pivalic acid. [51] The reaction (Scheme 105) gave 1,2,5-trisubstituted pyrrole 201 in 43% yield. In 2011, El Abed, Doucet and co-workers demonstrated that the PdClA C H T U N G T R E N N U N G (C 3 H 5 )A C H T U N G T R E N N U N G (dppb)-catalyzed reaction between 1.5 equiv.…”
Section: A C H T U N G T R E N N U N G (P-cymene)]/a C H T U N G T R mentioning
confidence: 99%
See 1 more Smart Citation